SRT1720 Alleviates ANIT-Induced Cholestasis in a Mouse Model - Yu, Linxi; Liu, Xiaoxin; Yuan, Zihang; Li, Xiaojiaoyang; Yang, Hang; Yuan, Ziqiao; Sun, Lixin; Zhang, Luyong; Jiang, Zhengzhou (Frontiers in Pharmacology, 2017)
Intrahepatic cholestasis is regarded clinically as a syndrome with intrahepatic and systemic accumulations of excessive bile acids that ultimately causes hepatotoxicity. Dysregulation of bile acid transporters, oxidative stress and inflammation are important generating factors in the pathogenesis of cholestasis. Mammalian SIRT1 is a class III histone deacetylase (HDAC), whose activation is dependent on nicotinamide adenine dinucleotide in the nucleus. Accumulating evidence has revealed that SIRT1 is crucial for the regulation of hepatic bile acid metabolism. The aim of the study is to clarify the protective effect of SRT1720，a specific activator of SIRT1 that is 1000 times more potent than resveratrol, on alpha-naphthylisothiocyanate (ANIT)-induced hepatotoxicity and cholestasis in mice. The results suggest that SRT1720 treatment protect against ANIT-induced hepatotoxicity and cholestasis by increasing FXR and Nrf2 gene expressions. It altered the gene and protein expressions of hepatic transporters involved in bile acid transport. Furthermore, SRT1720 enhanced the antioxidative system by increasing Nrf2, SOD, GCLc, GCLm, Nqo1 and HO-1 gene expressions. In conclusion, SRT1720 produced a protective effect against ANIT-induced hepatotoxicity and cholestasis, partly due to active FXR and Nrf2 expressions. The results indicated that SIRT1 might be a suitable therapeutic target for the treatment of cholestasis.